صناديق الإستثمار ودورها في سوق الأوراق المالية - حمدان فاطمة, حمدان عبد القادر (My University, 2022)
Invest boxes are considered as one of the most important financial innovations that were used widely all over the world. This study aims to show the significant role which is made by the investboxes for Saudi market.To answer all questions related to this study,we focused on gathering a group of information and datas that determine the theoretical frame of the study and the practical frame of Saudi market. Among the gethered findings ,the existence of positive relation and morale statistic between the variables,the progress of invest boxes(distinct variable) and indicator of Saudi marketshares performance( subsequent variable) of period (2010/2021),and this by relying on the programme EVEIWS 9 ; and estimating the parametres of the sample with a stable test for the time series and an integral and entrant test .
دراسة حالة السوق السعودي خلال الفترة 2010/2021
Keywords: :invest boxes,paper market, Saudi indicator marketshares performance.